2024 annual trends and outlook report: Advancing the climate and bioeconomy agenda in Africa for resilient and sustainable agrifood systems - Tadesse, Getaw; Glatzel, Katrin; Savadogo, Moumini (AKADEMIYA2063, 2024)
The 2024 edition of the Annual Trends and Outlook Report (ATOR) explores the challenges posed by the climate crisis to agrifood systems and the opportunities offered by a transition to a bioeconomy to mitigate and adapt to the adverse impacts of climate change. This ATOR seeks to support the ongoing development and the subsequent implementation of a new 10-year Comprehensive Africa Agriculture Development Programme (CAADP) strategy by the African Union through the renewed and updated post-Malabo CAADP agenda.